2017
DOI: 10.4269/ajtmh.16-0599
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and Zinc Supplementation Among Pregnant Women to Prevent Placental Malaria: A Randomized, Double-Blind, Placebo-Controlled Trial in Tanzania

Abstract: Vitamin A and zinc are important for immune function and may improve host defense against malaria and reduce the risk of adverse pregnancy outcomes. Our objective was to determine whether daily oral supplementation with either or both nutrients starting in the first trimester reduces the risk of placental malaria and adverse pregnancy outcomes. We undertook a randomized, double-blind placebo-controlled trial with a factorial design among 2,500 human immunodeficiency virus-negative primigravid or secundigravid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 28 publications
1
60
0
Order By: Relevance
“…Nine studies assessed vitamin A supplementation compared to placebo or no treatment [53,60,63,79,86,92,94,110,111]. Of these, one study was excluded from meta-analysis because it reported no poolable outcomes, but was narratively synthesized [53] (see Supplementary Materials, Table S3).…”
Section: Vitamin a Supplementation Versus Placebomentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies assessed vitamin A supplementation compared to placebo or no treatment [53,60,63,79,86,92,94,110,111]. Of these, one study was excluded from meta-analysis because it reported no poolable outcomes, but was narratively synthesized [53] (see Supplementary Materials, Table S3).…”
Section: Vitamin a Supplementation Versus Placebomentioning
confidence: 99%
“…Of these, one study was excluded from meta-analysis because it reported no poolable outcomes, but was narratively synthesized [53] (see Supplementary Materials, Table S3). Thus, eight studies were included in the meta-analyses [60,63,79,86,92,94,110,111]. Four of these studies were conducted in the sub-Saharan Africa-of which, two were in Ghana [79,86], one in Malawi [92] and one in Tanzania [94].…”
Section: Vitamin a Supplementation Versus Placebomentioning
confidence: 99%
“…Notably, we recently determined the prevalence of moderate vitamin A deficiency (defined as serum retinol <0.07 μmol/L) in Dar es Salam to be low (8%) in a separate pregnancy cohort (Masanja et al, ). In the parent trial, we found no effect of prenatal vitamin A on placental malaria, small‐for‐gestational age birth, or prematurity (Darling et al, ). As a result, the low level of deficiency in this population may have led to no effect of supplementation on maternal and child health, cognitive/language, and socioemotional outcomes.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, all women were given a daily dose of 60 mg of iron and 5 mg of folic acid in accordance with Tanzanian standard of care. The mean compliance rate across all women in the parent trial was 84.5% (median 97.6%; Darling et al, 2017).…”
Section: Study Populationmentioning
confidence: 99%
“…One article was added from the references of the included articles. Of these 58, 15 articles or 11 distinct studies/trials [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were finally selected for inclusion in this systematic review. The flow diagram of the literature search along with the reasons for 43 excluded studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%